Mut'ah Marriage in Islamic Perspective - Helandri, Joni; Achmad, Ghazimin; Supriadi, Supriadi (Indonesian Journal for Islamic Studies, 2023)
Mut'ah marriage is a form of temporary marriage that exists in Islamic tradition. From an Islamic perspective, mut'ah marriage has a complex history and social context. This study aims to analyze the practice of mutah marriage in the perspective of Islamic law and to look at the controversies and social impacts associated with it. The public's perception of mut'ah marriage varies, depending on the individual's understanding of religious teachings. The practice of mut'ah marriage also still exists in Muslim society, with different reasons and motivations. This study used a qualitative approach using a literature review. The conclusion of this paper underscores the importance of understanding mut'ah marriage in the Islamic context in depth. The implications of this research can be a reference for a better understanding of this practice, as well as providing recommendations for further research related to social and legal issues related to mut'ah marriage.